2013
DOI: 10.1080/15472450.2013.802160
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency and Robustness in a Support Platform for Intelligent Airport Ground Handling

Abstract: One of the effects of the development of air traffic during recent years is the increase of congestion on major airports and their aprons, where ground handling operations take place. Efficiency and safety issues become important on the aprons. The\ud “Integrated Airport Apron Safety Fleet Management – AAS” project aims at setting\ud a decision support system for an efficient and safe management of apron traffic,\ud taking advantage of information gathered by “intelligent” vehicles equipped with on-\ud board p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…We tested the performance of the algorithm on a case study involving four major European airports, namely, London Heathrow, Paris Charles De Gaulle, Amsterdam Schiphol and Frankfurt. Data were gathered from the Eurocontrol Demand Data Repository (DDR2), as described in [3]. We selected October 3 rd , 2016 because it was a busy day of the year.…”
Section: Computational Resultsmentioning
confidence: 99%
“…We tested the performance of the algorithm on a case study involving four major European airports, namely, London Heathrow, Paris Charles De Gaulle, Amsterdam Schiphol and Frankfurt. Data were gathered from the Eurocontrol Demand Data Repository (DDR2), as described in [3]. We selected October 3 rd , 2016 because it was a busy day of the year.…”
Section: Computational Resultsmentioning
confidence: 99%
“…Another line of research analyzes safety issues in airports, which are captured by the interplay between air and ground vehicles or the use of civil drones [18], [19]. Other less related works for manpower scheduling or airside operation research can be found in [20], [21], [22], [23].…”
Section: A Airport Ground Handlingmentioning
confidence: 99%
“…By applying their approach, Kuhn and Loth [25] achieved a 20% reduction in aircraft delays and the distance traveled by service vehicles. Andreatta et al [26] proposed a mathematical formulation and a sequential heuristic for optimizing the assignment of vehicles to apron ground service operations. They incorporated various factors that can disrupt the operation of ground services, such as aircraft delays.…”
Section: Related Literaturementioning
confidence: 99%